Isolation of Campylobacter hepaticus from free-range poultry with spotty liver disease in New Zealand. Issue 1 (2nd January 2021) - Crawshaw, TR; Hunter, S; Wilkinson, DA; Rogers, LE; Christensen, NH; Midwinter, AC
ABSTRACT: Case history: In October 2019, a free-range egg laying flock suffering an outbreak of spotty liver disease was investigated. Eight 32-week-old hens were examined post-mortem. Clinical and pathological findings: Five of the eight hens had sparse, focal, gross hepatic lesions typical of spotty liver disease. Histopathology of the liver showed random, focal hepatic necrosis, lymphoplasmacytic cholangitis/pericholangitis and, in one hen, severe lymphoplasmacytic cholecystitis. Campylobacter -like organisms were grown from all eight bile samples which were confirmed by PCR as Campylobacter hepaticus . The genome of C. hepaticus isolates from the outbreak were sequenced and compared to those of isolates from Australia and the United Kingdom. Phylogenetic analysis based on single nucleotide polymorphisms showed that the C. hepaticus isolates from this outbreak were most closely related to isolates from Australia. Diagnosis: Campylobacter hepaticus focal hepatic necrosis. Clinical relevance: This is the first report of an outbreak of spotty liver disease confirmed to be caused by C. hepaticus in poultry in New Zealand. Therefore infection with C. hepaticus should be considered as a differential diagnosis for mortality in laying hens around peak lay in New Zealand.